Understanding the interactions of residual chemical fertilizers with vitamin B3 via conductometric and spectroscopic studies - Prachiprava Mohapatra; Tanika Dutta; Siddhartha Panda; Sulochana Singh; Malabika Talukdar (BMC Chemistry)
Abstract This work aims to provide a basic understanding of how the excessive use of chemical fertilizers affects the nutrition levels of soil, plants, green vegetables and fruits. While the plant can initially "withstand" the excess fertilizer through increased protein synthesis; the remaining is accumulated in the form of nitrates and high nitrate concentrations in edible tissues of plants can pose health risks, such as affecting the oxygen-carrying capacity of blood in humans or animals. Objective of this work is to understand various molecular interactions occurring between different solution-components with each other and with water. The present study is based on conductometric evaluation of a ternary system of vitamin B3 (Nicotinamide, NAD) and fertilizers (Potassium Chloride, KCl and Diammonium hydrogen phosphate, DAP) in aqueous medium with varying concentration within a temperature range of 293.15 to 313.15 K. The conductivity data has been used to compute molar conductance $$({\bigwedge }_{m})$$ ( ⋀ m ) and Walden factor $$({\bigwedge }_{m}^{0}{η }_{0})$$ ( ⋀ m 0 η 0 ) to understand the conducting behaviour of the experimental solutions. Thermodynamic parameters like changes in Gibbs free energy ( $${Δ G}^{0}$$ Δ G 0 ), enthalpy ( $${Δ H}^{0})$$ Δ H 0 ) and entropy $${(Δ S}^{0})$$ ( Δ S 0 ) for ion association were calculated to understand the feasibility and spontaneity of the process. As charged particles need to overcome an energy barrier to migrate through the solution, activation energy for charge mobility is also estimated. These parameters were qualitatively correlated with changes in structure of water that occurs when nicotinamideinteracts with $$DAP/KCl$$ D A P / K C l in aqueous medium.